Effect of adding perlite the soil in reducing water stress and its effect in some characteristics of the yield of three Genotypes of tomato
The experiment was conducted during spring season of 2016 on the field of State Board of Agric., department of horticulture and landscape, college of agriculture, university of Diyala, Iraq. The objective of the experiment was investigated the interaction of three factors, three tomato Genotypes